PERBANDINGAN BERBAGAI MIKROORGANISME LOKAL (MOL) PADA PROSES PENGOMPOSAN SECARA ANAEROBIK: Comparison of Various Local Microorganisms (MOL) in Anaerobic Composting Process - Kamarullah, Novitasari; Dwi Wahyu Purwiningsih; H, Haikun; Laudo, Karmila; Bano, Efirufini H.; Derlen, Zainy Azhary (JURNAL ILMU DAN TEKNOLOGI KESEHATAN TERPADU, 2021)
Garbage is solid waste consisting of organic and inorganic substances which are considered useless and must be managed. Composting is a method of converting organic materials into simpler materials using microbial activity. MOL is a group of micro-organisms that function as a "starter" in making compost. In this study, discussed the comparison of the ability of various local microorganisms (MOL) in the Anaerobic Composting process. This study aimed to provide benefits to the community in utilizing waste. This type of research is experimental, namely, the comparison which aims to determine the length of time composting and the amount of compost produced. The research location was conducted in Sangaji Urban Village. The research sample was a sample of various kinds of local microorganisms. Organic wastes used such as fruits, vegetables, food scraps, and a mixture of other organic waste, each as much as 20 kg. The fastest composting between the 5 compost spices and the control for the longest composting time was stale rice MOL which was 10 days and the most compost produced was shrimp paste MOL which was 6 kg. The length of time needed for the 5 compost spices and controls is Â± 1-2 weeks.